TRANSFORMATION OF THE EPILEPTIC SYSTEM. CURRENT STATUS OF THE PROBLEM AND POSSIBLE WAYS TO SOLVE IT - G. N. Avakyan; G. G. Avakyan (Эпилепсия и пароксизмальные состояния, 2017)
We have conducted an experiment with valproic acid drugs (used as an example), where we have identified the determinant and dominant structures of the epileptic system. The main determinant structure is hypothalamus; it is responsible for secondary generalized seizures formation. The next strusctures in the hierarchy are contralateral and ipsilateral hippocampus, contralateral cortex. Collateral subordination of the structures and the transformation of the epileptic pathological system has been revealed. We demonstrated the advantages of the Depakin Chronosphere microgranules and effectiveness of the drug for treating children, adolescents, adults and elderly patients with epilepsy. The results of experimental studies with Nano-Phenazepam substantiate its further development as an antiepileptic drug for the treatment of secondary generalized seizures and prevention of status epilepticus. To optimize the surgical treatment of pharmacoresistant epilepsies, it is necessary to use minimally invasive functional neurosurgical techniques and/or their combination in each individual patient.